Optimizing Production Quantities of Perishable Products Based on Demand Patterns Using Time Series Analysis and the Newsboy Problem at Muun Donuts Lhokseumawe - Gilang Afandi; Diana Khairani Sofyan; Khairul Anshar (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Muun Donuts in Lhokseumawe is a producer of fresh donuts (a perishable product) that faces daily operational challenges in the form of unpredictable fluctuations in daily demand. The lack of a standard numerical benchmark for determining daily production capacity creates the risk of dual losses, such as waste of raw materials (overstock) and loss of potential profit (stockout). The objective of this study is to determine the optimal production volume and predict the expected maximum profit. This study integrates a time series forecasting approach with the newsboy problem method. The results show that the optimal single-base production quantity for the company is 24,550 pcs. The distribution of optimal production allocation per period throughout 2026 ranges from 23,902 pcs to 25,199 pcs per month, equivalent to an average daily dough conversion of 14 kg to 16 kg per day. Aggregately, the implementation of this proposed integrated method is projected to generate a total expected profit of IDR 1,119,489,296 per year, or yield an annual total profit increase of IDR 25,914,296 compared to the company’s current policy. This stochastic approach has proven effective as a foundation for management’s tactical decisions to reduce food waste while maintaining the quality of customer service.